Amyotrophic Lateral Sclerosis: Review - Salameh, Johnny S.; Brown, Robert H., Jr.; Berry, James D. (Seminars in Neurology, 2015)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease primarily affecting the upper and lower motor neurons. The lifetime risk of developing ALS is estimated at 1:350 for men and 1:500 for women, higher for those who have served in the military. The diagnosis remains clinical with electrodiagnostic support. Alternative diagnoses can usually be ruled out by the use of neuroimaging studies and laboratory evaluation. Perhaps because ALS is a diagnosis of exclusion, there is a substantial delay in diagnosis, upward of 12 months after the onset of symptoms, and most patients see three or more providers in the course of the diagnostic process. Once diagnosed, patients are best medically managed in a multidisciplinary care setting, an approach that has been shown to prolong survival and improve quality of life. Riluzole is the only disease-modifying therapy approved by the Food and Drug Administration, but numerous symptomatic therapies exist. In the past 20 years, ALS has become the focus of intense investigation by a worldwide community of basic scientists, and for clinical investigators the disease is an active area of research, with stem cell therapies, gene therapies, and a host of small molecule agents under investigation at various stages of clinical and preclinical development.
Keywords: amyotrophic lateral sclerosis; motor neuron disease; multidisciplinary care